PEDAGOGICALLY MEDIATED YOUTUBE INTEGRATION FOR INTERACTIVE LEARNING IN EARLY CHILDHOOD EDUCATION - Deviani, Risma; Hasanah, Hisbiyatul; Priatiningsih , Selasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine how YouTube channels are utilized as interactive learning media for children aged 4–5 years at TK PGRI Kartini Ledokombo, Jember. Although previous studies have confirmed the effectiveness of YouTube in improving children's motivation and learning outcomes, limited attention has been given to the pedagogical processes through which teachers select educational content, facilitate classroom interaction, and sustain children's engagement during learning. This study advances a pedagogically mediated digital learning perspective by conceptualizing YouTube as an interactive learning ecosystem rather than merely an audiovisual medium. Empirical evidence further shows that 11 of 15 children actively participated in classroom discussions, while 8 children successfully reconstructed learning content using their own words. This study employed a qualitative descriptive approach involving one principal, one classroom teacher, 15 children aged 4–5 years, and several parents selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. Source and method triangulation were applied to enhance the credibility of the findings. The findings indicate that effective YouTube integration depends on systematic instructional planning, teacher mediation, and continuous classroom interaction rather than the technological features of the platform itself. Children's positive responses were reflected in sustained attention, active participation, improved conceptual understanding, and collaborative communication. The study demonstrates that meaningful digital learning emerges through the dynamic interaction among teachers, learners, instructional design, and multimedia resources, providing a broader conceptual understanding of interactive digital pedagogy in early childhood education.